2005
DOI: 10.1111/j.1365-2427.2005.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Additive partitioning of aquatic invertebrate species diversity across multiple spatial scales

Abstract: 1. Additive partitioning of three measures of diversity (species richness, Shannon's diversity index H and Simpson's diversity D) was used to study the relationship between local and regional diversity of benthic macroinvertebrate communities of boreal lakes (littoral habitats) and streams (riffle habitats) across three spatial scales (sampling sites, ecoregions and biogeographic regions). 2. Alpha (a) and beta (b) diversity are defined as within-habitat and between-habitat diversity, respectively. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
108
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 53 publications
9
108
3
2
Order By: Relevance
“…This suggests that a connection between habitat patches influences species composition at a regional scale. Our findings of a high contribution of b diversity and low contribution of a diversity to regional c diversity are consistent with previous studies of freshwater fishes and invertebrates (Stendera andJohnson 2005, Eros 2007) and terrestrial plants (Clough et al 2007). High dissimilarity between habitat patches has been explained by a strong dispersal limitation between the patches as well as a strong species-sorting process by environmental filters or competition (Capers et al 2010, Clarke et al 2010, Matthiessen et al 2010.…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that a connection between habitat patches influences species composition at a regional scale. Our findings of a high contribution of b diversity and low contribution of a diversity to regional c diversity are consistent with previous studies of freshwater fishes and invertebrates (Stendera andJohnson 2005, Eros 2007) and terrestrial plants (Clough et al 2007). High dissimilarity between habitat patches has been explained by a strong dispersal limitation between the patches as well as a strong species-sorting process by environmental filters or competition (Capers et al 2010, Clarke et al 2010, Matthiessen et al 2010.…”
Section: Discussionsupporting
confidence: 81%
“…De la misma manera, Cardoso de Ávila, Stenert & Maltchik (2011) y Stendera & Johnson (2005), encontraron que las escalas o filtros espaciales mayores son los que definen el cambio en la composición de macroinvertebrados acuáticos en sistemas dulceacuícolas y no los filtros relacionados con las escalas más finas (Ligeiro et al, 2009). En la cuenca del Río Xichú existe una alta diversidad β espacial y temporal de coleópteros e insectos hemimetábolos, debida a los bajos valores de similitud entre sitios de muestreo (I J <0.65) y altos valores de diversidad β en la partición multiescalar.…”
Section: Discussionunclassified
“…Estos filtros varían desde el nivel de cuenca hasta el de microhábitat e influyen sobre las comunidades de macroinvertebrados acuáti-cos en sistemas dulceacuícolas (Stendera & Johnson, 2005;Ligeiro, Melo & Callisto, 2009;Cardoso de Ávila, Stenert & Maltchik, 2011). La cuenca es una escala natural bien delimitada, con procesos y características propias: geomorfológicas, hidrológicas, climáticas y de uso de suelo, entre otras.…”
unclassified
“…The influence of local and regional factors driving species diversity has been recently discussed in different biological communities (Bini et al, 2003;Stendera and Johnson, 2005;Johnson et al, 2007). Studies describing assemblages of benthic macroinvertebrates have observed that local processes may be more important for the structure of these communities than regional processes (Stendera and Johnson, 2005;Johnson et al, 2007), and the factors may indeed be independent (Johnson and Goedkoop, 2002).…”
Section: Discussionmentioning
confidence: 99%